Breaking The Spell: Hilangnya Superioritas Laki-laki dalam Dua Film Produksi Walt Disney Pictures Frozen (2013) dan Maleficent (2014) - Ni Made Widisanti S; Shita Dewi Ratih (Universitas Pakuan, 2018)
AbstractFemale figures in the WDP films are mostly portrayed visually as women who live and are in the order of patriarchal society. The image of women and their relationship with social interaction in the WDP films are reviewed using visual methodology related to visual culture as a form of concern for how images, in this case, scene images, in the WDP films in the past and present context, can visualize social differences. The findings obtained through this study are the link between the periodization of Walt Disney Studios development with the production and the context of the films. The films, Frozen and Maleficent, as primary objects of this research are studied in order to answer the problem of social interaction between men and women and what discourse is built through the realtionship of social interaction. It was concluded that the relationship of social interaction displayed in the films Frozen and Maleficent was the interaction between women and women as a form of social relations that can be constructed. This also shows that social construction is dynamic because it can experience change over time, which in this research, is shown by the periodization of Walt Disney Studios development and its relationship with the context in the films. The character of the socially constructed superordinate and subordinate nature is proven to be interchangeable through visual culture. Therefore, based on these findings, it can be said that the discourse of these two films is the effort of women to free themselves from the oprression of male power despite the life of the patriarchal society. Key Words: Film, image, women, superordinate-subordinate, social interactions